Templated Out‐of‐Equilibrium Self‐Assembly of Branched Au Nanoshells (Small 12/2023). Issue 12 (22nd March 2023) - Marchetti, Alessandro; Gori, Alessandro; Ferretti, Anna Maria; Esteban, Daniel Arenas; Bals, Sara; Pigliacelli, Claudia; Metrangolo, Pierangelo
Abstract : Branched Au Nanoshells Out‐of‐equilibrium self‐assembly of metal nanoparticles achieving 3D structures with controlled morphology is still rare. In article number 2206712, Claudia Pigliacelli, Pierangelo Metrangolo, and co‐workers adopt a peptide‐gold superstructure as template to control the out‐of‐equilibrium self‐assembly of Au nanoparticles, obtaining a transient 3D branched Au‐nanoshell stabilized by surfactant. The nanoshell dismantles upon concentration gradient equilibration, leading to disassembly and regression to the template.